Doing Business in Hargeisa 2012 - World Bank; International Finance Corporation (Washington, DC, 2013)
Doing Business in Hargeisa 2012 measures business regulations and their enforcement in Hargeisa, Somaliland. It is the first Doing Business city profile in Somaliland. Comparisons with other economies are based on Doing Business 2012, doing business in a more transparent world, the ninth in a series of annual reports published by the World Bank and International Finance Corporation. The indicators in Doing Business in Hargeisa 2012 are also comparable with 335 cities from 54 economies benchmarked in other subnational Doing Business studies. Doing Business investigates the regulations that enhance business activity and those that constrain it. Doing Business in Hargeisa 2012 measures regulations affecting 11 stages of the life of a small or medium-size business: starting a business, dealing with construction permits, getting electricity, registering property, getting credit, protecting investors, paying taxes, trading across borders, enforcing contracts, and resolving insolvency. Data on the employing workers indicator is available as an annex. The data in Doing Business in Hargeisa 2012 are current as of May 2012.